Pump Installation for Groundwater Utilization at Islamic Boarding School of Miftahul Jannah Putri Pamanjengan, Moncongloe - Maros - Muhammad - Ramli; Purwanto Purwanto; Aryanti Virtanti Anas; Rini Novrianti Sutardjo; Nirmana Fiqra Qaidahiyani; Asta Arjunoarwan Hatta; Irzal Nur; Sri Widodo; Sufriadin Sufriadin; Rizki Amalia (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2023)
This community service activity has been carried out at the Miftahul Jannah Putri Tahfidzul Qur'an Islamic Boarding School in Pamanjengan, Moncongloe, Maros Regency. This Islamic Boarding School for Qur’an Memorizer fosters 10 children from families with underprivileged economic conditions. The capacity of the pondok buildings can accommodate more number of students, but water supply is a big problem. Therefore, the management of the school has attempted to add groundwater production wells through financing from other parties. Drilling was carried out to a depth of 60 meters. The well pumping test with a discharge of 1,440 liters/hour showed a change in the groundwater level to become static at a decrease of 1.60 meters. Thus, the condition prior to this community service activity was that there were production wells but had not been equipped with submersible pump wells. Information from the pre-test indicated that the students still felt limited clean water. Therefore, through Hasanuddin University's P2C-IKU activities, pump installations are carried out to be able to utilize groundwater from the drilled wells. The results of the post-test at the end of this activity showed that 83.30% of respondents believed that there would be sufficient water supply to meet the needs of the cottage, and 57.14% of respondents understood how to operate and maintain submersible pumps.